An intrusion tolerant system architecture for secure and self-healing smart grid control centers - Tanha, Maryam (2013)
The ever-increasing, novel and sophisticated cyber threats underscore the need for more robust and resilient security approaches. The situation would be further aggravated due to the dependence of many critical infrastructures on information and communication technology. Critical infrastructures require automatic response and self-healing capabilities to handle multifarious malicious attacks while remaining survivable and secure. The cyber security is of great importance for critical infrastructures due to far-reaching societal and economic impacts caused by failure or malfunction of their key components (in particular, control centers) resulting from malicious attacks on the communication infrastructure. Unfortunately,conventional security mechanisms, namely prevention and detection systems have limitations to suffice for the crucial operation of critical infrastructures such as smart grid. For this reason, a new security paradigm referred to as intrusion tolerance needs to be incorporated into critical infrastructures. The intrusion tolerance is envisaged to complement the existing security solutions,as well as to provide availability (as the top security priority) and self-healing capabilities for control centers of critical infrastructures. However, intrusion tolerance techniques are associated with substantial cost. This dissertation proposes an intrusion tolerant system architecture which incorporates distinctive features,namely hybrid and hierarchical rejuvenation mechanism as well as dynamic redundancy level. The aforementioned characteristics are formulated in such a way to decrease the incurred intrusion tolerance cost while improving security. The security of the proposed architecture is analytically evaluated, and the acquired results show improvements compared to two established intrusion tolerant system architectures. The incurred cost in terms of overhead is also analyzed, and the outcomes demonstrate the cost-effectiveness of the proposed architecture.